Book review: Maryam Wasif Khan, Who Is a Muslim? Orientalism and Literary Populisms. (April 2023) - Naz, Farhat
Maryam Wasif Khan, Who Is a Muslim? Orientalism and Literary Populisms (Hyderabad: Orient BlackSwan, 2021), 257 pp., ₹1025. ISBN: 978-9-3544-2046-7 (Hardback).